The effect of coincidental SARS‐CoV‐2 infection on pre‐operative cardiopulmonary exercise testing. Issue 1 (9th June 2021) - Whitfield, C.; Adamson, M.; Davies, R.
Summary: This case report demonstrates the significant impact active infection with SARS‐CoV‐2 can have on functional capacity evaluated by cardiopulmonary exercise testing, even in minimally symptomatic individuals. A 75‐year‐old man underwent cardiopulmonary exercise testing before a right hemicolectomy; SARS‐CoV‐2 was incidentally diagnosed following his test. The patient underwent a period of isolation and recovery before a second pre‐operative cardiopulmonary exercise test 6 weeks later. His resting pulmonary function tests did not vary between tests but his peak work, anaerobic threshold, oxygen pulse, pulse oximetry nadir, ventilation perfusion matching and heart rate response to exercise all improved significantly after this recovery period. These are unique results that add to the existing knowledge of the pathophysiology and management of SARS‐CoV‐2 in the peri‐operative setting. While our patient demonstrated dramatic improvement in his functional capacity following 6 weeks of recovery, he remained in a high‐risk group for surgery according to our local guidelines. Cardiopulmonary exercise testing has a valuable role in individualised risk assessment and shared decision‐making in complex, urgent surgical cases where the benefits of delaying surgery to recover from SARS‐CoV‐2 infection should be balanced against the potential risks.